Epistemic feelings, epistemic emotions : review and introduction to the focus section (2014)
ABSTRACT: Philosophers of mind and epistemologists are increasingly making room in their theories for epistemic emotions (E-emotions) and, drawing on metacognition research in psychology, epistemic – or noetic or metacognitive – feelings (E-feelings). Since philosophers have only recently begun to draw on empirical research on E-feelings, in particular, we begin by providing a general characterization of E-feelings (section 1) and reviewing some highlights of relevant research (section 2). We then turn to philosophical work on E-feelings and E-emotions, situating the contributions to the focus section (two articles devoted to E-feelings and two devoted to E-emotions) with respect to both the existing literature and each other (section 3). We conclude by briefly describing some promising avenues for further philosophical research on E-feelings and E-emotions (section 4).